Opposite Effect Of Inflammation on SVZ vs. Hippocampal Precursors In Brain Injury - Covey, Matthew V. (2011)
OBJECTIVE: Inflammation promotes epidermal wound healing but is considered detrimental to recovery from CNS injury. Sick infants have increased levels of cytokines in their CSF that correlate with poor neurological outcome. In this study we investigated the role of neuroinflammation and more specifically, IL-6, in the amplification of subventricular zone (SVZ) and subgranular zone (SGZ) neural precursors after neonatal brain injury. METHODS: Neonatal hypoxia/ischemia (H/I) was induced in P6 rat pups and IL-6 was quantified with or without Indomethacin administration. Neural precursor responses were evaluated by neurosphere assays as well as by stereological analyses. Studies were performed to determine how IL-6 and LIF affect SVZ cell expansion, proliferation and self-renewal. RESULTS: Consistent with earlier studies, SVZ cells expanded after H/I. Contrary to our expectations, Indomethacin significantly decreased both the initial reactive increase in these precursors as well as their ability to self-renew. By contrast, Indomethacin increased proliferation in the SGZ and lateral SVZ. Indomethacin diminished the accumulation of microglia/macrophages and IL-6 production after H/I. In vitro IL-6 enhanced neurosphere growth, self-renewal and tripotentiality and was more effective than LIF in promoting self-renewal. Enhanced precursor self-renewal also was obtained using PGE(2), which is downstream of cyclooxygenase-2 and a target of Indomethacin. INTERPRETATION: These data implicate neuroinflammation and in particular IL-6 as a positive effector of primitive neural precursor expansion after neonatal brain injury. These findings have important clinical implications, as Indomethacin and other anti-inflammatory agents are administered to premature infants for a variety of reasons.